2000
DOI: 10.2169/internalmedicine.39.433
|View full text |Cite
|
Sign up to set email alerts
|

Paragonimiasis Westermani with Multifocal Lesions in Lungs and Skin.

Abstract: Wereport a case of Paragonimuswestermaniinfection with a reticulonodular lesion in the right lung, left pleural effusion, and a mobile subcutaneous mass. Analyses of pleural effusion and bronchoalveolar lavage fluid (BALF) showed marked eosinophilia and high levels of eosinophil cationic protein and interleukin (IL)-5. Transbronchial lung biopsy revealed the presence of pneumonia with mild eosinophilic infiltration but remarkable lymphocytic infiltration. In this patient, high IL-5 levels in both BALF and pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…In contrast Singh and coworkers reported a higher prevalence among male patients in Manipur, India [15]. However, paragonimiasis is found in children, adults, and all categories of people [14]. On the whole, crab eating is common in Eastern Nigeria.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast Singh and coworkers reported a higher prevalence among male patients in Manipur, India [15]. However, paragonimiasis is found in children, adults, and all categories of people [14]. On the whole, crab eating is common in Eastern Nigeria.…”
Section: Discussionmentioning
confidence: 93%
“…However, prevalence was comparable between both sexes in neighboring southwest area of Cameroon [9]. Many other researchers have reported no sex-related difference in prevalence [13,14]. In contrast Singh and coworkers reported a higher prevalence among male patients in Manipur, India [15].…”
Section: Discussionmentioning
confidence: 99%
“…Uchiyama et al reviewed 104 patients with paragonimiasis from 1986 to 1998 and demonstrated that children as well as adults were infected and that there was no substantial difference in the male-to-female ratio (182). Ashitani et al also reported paragonimiasis in children as well as adults and failed to demonstrate any obvious distributional differences with respect to sex (9). Some have suggested that children in some areas may be infected at a higher rate than adults.…”
Section: Epidemiology Of Human Diseasementioning
confidence: 98%
“…It has been suggested that aberrant migration is more likely to occur in heavy infections (9,126). The migrating immature parasites may come to rest in a variety of organs.…”
Section: Ectopic Paragonimiasismentioning
confidence: 99%
“…This too agrees with the reports made by (Singh et al, 1986;Udonsi 1987;Uttah et al, 2013) but disagrees with the results of (Ibenga et al, 1997;Asor et al, 2003;Uttah, 2013) who reported that more females were infected than males. Many other researchers have reported no sex-related difference in prevalence (Uchiyama et al, 1999;Ashitani et al, 2000). It is pertinent to note that, although both sexes can acquire the infection through food or by wrong sense of remedy to certain ailments, the males encounter crabs more than females.…”
Section: Resultsmentioning
confidence: 89%